Mechanistic Studies on the Rearrangement of 1‐Alkenyl‐2‐alkynylcyclopropanes: From Allylic Gold(I) Cations to Stable Carbocations1. Issue 45 (15th September 2014) - Tudela, Eva; González, Jairo; Vicente, Rubén; Santamaría, Javier; Rodríguez, Miguel A.; Ballesteros, Alfredo
Abstract An allylic gold(I) cation, proposed as key intermediate in the gold‐promoted rearrangement of 1, 5‐enynes bearing a fixed conformation, has been detected and characterized by NMR spectroscopy. Moreover, its participation in the overall transformation was confirmed. Computational studies indicate that the gold‐catalyzed transformation occurs through an uncommon rearrangement. Additionally, this study led us to isolate and characterize a stable homoantiaromatic carbocation.